Expression of the late gene of simian virus 40 under the control of the simian virus 40 early-region promoter in monkey and mouse cells. - Rao, V N (1986)
We constructed a recombinant plasmid (pVNR4) with the simian virus 40 (SV40) early promoter positioned 30 nucleotides upstream from the major SV40 late transcription initiation site at residue 325. After transfection of the recombinant plasmid DNA into COS and mouse L cells, the transcripts of the SV40 late region were analyzed by S1 nuclease and primer extension analysis. The following are the principal findings. (i) The 16S and 19S late RNAs used the characteristic wild-type splice; no detectable levels of 19S unspliced RNA were observed. (ii) The majority of the late RNAs were heterogeneous and initiated in the early region (upstream and downstream from the Hogness-Goldberg sequence), and a minor population initiated at residue 325, the principal 5' terminus of the wild-type late RNA. (iii) During SV40 lytic infection there was a shift in initiation sites used to transcribe the early region from sites that are downstream to sites which are upstream (up RNA) of the origin of DNA replication. We observed that unlike lytic infection, T antigen and viral DNA replication were not needed for the appearance of up RNA in mouse L cells. (iv) In mouse L cells late RNAs were made, and the residue 325 5' end was utilized in the absence of T antigen or DNA replication. (v) In COS cells we found down RNA and up RNA transcribed from the extrachromosomally replicating plasmid but only down RNA produced by the integrated SV40 genome.